The benar relaxation therapy (BRT) for increasing sleep quality in diabetic type II At Pakem primary health centre - Hidayati, Rizqi Wahyu; Rukmi, Dwi Kartika (MEDIA ILMU KESEHATAN, 2024)
Background: Insomnia was 4.3 times more risky improving blood glucose. Nowadays, 60% of diabetes type II patients are insomnia. Sleep regulates the hormones and regulation of glucose. Poor glucose regulation has aneffect on obesity, which increases the risk of diabetes complications. Purpose: To evaluate the effect of Benar Relaxation Therapy (BRT) on increasing sleep quality in diabetes patients. Method: This study was a Quasi-experimental method with a pre-posttest control group design—the 37 adults with type II diabetic patients. The patients who had got ADLs independently in Pakem Primary Health Centre followed this study. Both the BRT and aromatherapy needed 3 days long and got 15 minutes for one session each day. PSQI was used to measure the sleep quality of the respondents. The Friedman was used to test statistically. Result: Based on the result, it showed that the p-value 0.02 (p<0.05) for the intervention group with the Post Hoc result pre–post 1 was 0.017; pre-post 2 was 0.006; and pre-post 3 was0.009 (p<0.05). However, the control group was 0.188 (p>0.05). Conclusion: Benar Relaxation Therapy significantly increases sleep quality with one session minimum intervention. This therapy can be implemented in nursing practice who have insomnia, especially patients with type II diabetes